Southeast Asia Happiness Report in 2020 Using Exploratory Data Analysis - Riyantoko, Prismahardi Aji (International Journal of Computer, Network Security and Information System, 2020)
The happiness index to be one of part to presents that each country has indicator which affect each other. Many countries have a basic indicator to determine that happiness score, there are economy sector, social support, trust to the government, generosity, and measure life satisfactions. The indicator is presents in the dataset, it means need to explore, analysis, and visualization to give knowledge to the other people. Data science is one knowledge field to determine data. Exploratory data analysis (EDA) is part of data science process. In this works, we present happiness report in the Southeast Asia region using the dataset World Happiness Report 2020. The results, we describe and discuss the dataset using table with column and value or score, the other we using bar-plot, correlation bar-plot, bar-plot analysis, and map-plotting visualization. Output of EDA is only recommendation to next parts in the Data Science process, minimum has knowledge to reducing data, merge data, cleansing data, visualization data to be based of knowledge to build data modelling.